Pengaruh Penggunaan Sumber Silika Alumina Terhadap Karakteristik Semen yang Dihasilkan - Mawardi Mawardi; Rianti Sihaloho; Bahrizal Bahrizal (Jurnal Periodic Jurusan Kimia UNP, 2012)
A study concerning about the effect using of source silica alumina that shape napa land from Solok Selatan to characterization of cement produce. In this study can learning the effect using napa land to particle size of cement with tested the waste on sifter, not soluble, lose glowing, press force and composition chemichal of cement with XRF based variety composition is 0%, 5% dan 9.5% from total number of cement. Then the results are particle size, not soluble part and lose glowing of cement that produces increase as a increase using of napa land. However, not be valid on press force in 3, 7 and 28 days tested produce decrease. It caused the particle size of cement is increase as a increase of napa land composition. The largest using is 9.5% of total number of cement can be fill SNI standard 15-7064-2004.